Wear Characteristics of Fluorocarbon Thin Films Deposited Using Inductively Coupled and Capacitively Coupled Plasma Methods - Cho, Youn-Jeong; Jang, Yun Jung; Han, Seunghee; Lee, Yeonhee (AMER SCIENTIFIC PUBLISHERS, 2016)
Fluorocarbon thin films were fabricated using two different plasma polymerization techniques with the aim of improving the surface properties of various materials. The plasma-polymerized fluorocarbon thin films were produced using inductively coupled plasma (ICP) and capacitively coupled plasma (CCP) techniques with C2F6 and C3F8 precursors and different processing times. The surfaces of the resulting polymer films were investigated using water contact angle measurements, atomic force microscopy (AFM), and time-of-flight secondary ion mass spectrometry (TOF-SIMS) to obtain information on the hydrophobic properties, surface morphology, and chemical composition of the materials. The fluorocarbon thin films produced by the ICP technique showed greater hydrophobicity and more fluorinated functional groups than did those produced by the CCP technique. The wear of the fluorocarbon thin films was characterized using a ball-on-disk tribometer as well as lateral force microscopy (LFM). The wear test and microscopy results showed that the fluorocarbon thin films deposited using CCP exhibited lower friction coefficients and lower friction forces than those of the films deposited using ICP, indicating that the CCP technique produces fluorocarbon thin films with better microscale and nanoscale wear properties.
Keywords: BEHAVIOR